Different Bilingual Experiences Might Modulate Executive Tasks Advantages: Comparative Analysis between Monolinguals, Translators, and Interpreters - Henrard, Sébastien; Van Daele, Agnès (Frontiers in Psychology, 2017)
Many studies have shown that being bilingual presents an advantage in executive control. However, it appears that knowing two (or more) languages is not enough to improve executive control. According to the adaptive control hypothesis (Green and Abutalebi, 2013), the interactional context in which bilinguals behave is a key factor that modulates cognitive advantage in executive control. Translation and simultaneous interpretation are performed in a dual-language context: professional bi- and multilinguals use two or more languages within the same context (at work). Simultaneous interpretation differs from translation though, because of its higher level of time pressure, which increases the cognitive demands on executive control. The main objective of the present study is to investigate the relationship between simultaneous interpretation and some aspects of executive control. To this end, we compare the performance of three groups (60 interpreters, 60 translators and 60 monolinguals) in five computerised tasks designed to assess different executive processes as well as the speed of information processing. The results show that the interpreters perform better than the monolinguals in all tasks and better than the translators in all tasks except for the one designed to assess flexibility. The results also show that the age variable does not have the same effect on performance in tasks designed to assess updating, flexibility and resistance of proactive inhibition in bilinguals (both interpreters and translators), or in tasks designed to assess the speed of information processing and inhibition of a prepotent response in interpreters only. In addition to the advantage that being bilingual presents in some aspects of executive control, the results suggest that interpreters have an additional advantage that may be explained by the characteristics of their work activity (especially heavy time pressure) and by how much experience they have in this activity (in terms of magnitude of the bilingual management demands and amount of experience in managing the cognitive demands of simultaneous interpretation).